The Relationships Between Career-Related Emotional Support From Parents and Teachers and Career Adaptability - Song, Yuan; Mu, Fang; Zhang, Jiahong; Fu, Mingchen (Frontiers in Psychology, 2022)
Career-related support from parents and teachers plays an essential role in the process of promoting young people’s career development. This study examined the relationship between parents’ and teachers’ career-related support and career adaptability among Chinese male primary school preservice teachers (N=772). The participants completed the Career Adapt-Abilities Scale–Short Version (CAAS), the Career-Related Parental Support Scale (CRPSS) and the Career-Related Teacher Support Scale (CRTSS). Results showed that a high level of emotional support from parents and teachers had more effects on the career adaptability of Chinese male primary school preservice teachers then other aspects in the scale, and teachers' emotional support is more important than parents' emotional support. Notably, there is a complex correlation between parents' education level and occupation and children's occupational adaptability. These findings carry implications for supporting teachers and parents in facilitating preservice teachers’ career adaptability. Future research could identify the differential effects of different forms of teacher support and parental support relate to career adaptability.